2021
DOI: 10.1007/s40820-021-00698-0
|View full text |Cite
|
Sign up to set email alerts
|

High-Defect-Density Graphite for Superior-Performance Aluminum-Ion Batteries with Ultra-Fast Charging and Stable Long Life

Abstract: Rechargeable aluminum-ion batteries (AIBs) are a new generation of low-cost and large-scale electrical energy storage systems. However, AIBs suffer from a lack of reliable cathode materials with insufficient intercalation sites, poor ion-conducting channels, and poor diffusion dynamics of large chloroaluminate anions (AlCl4− and Al2Cl7−). To address these issues, surface-modified graphitic carbon materials [i.e., acid-treated expanded graphite (AEG) and base-etched graphite (BEG)] are developed as novel cathod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 68 publications
(102 reference statements)
3
39
0
Order By: Relevance
“…A b -value of 0.5 indicates a diffusion-controlled process, whereas a b -value of 1 represents ideal surface-controlled capacitive behavior. The value of b can be obtained from the slope of the linear relationship between log­( i ) and log­( v ) plots according to the following equation Figure b shows the relationship between log­( i ) and log­( v ), where the linear slope represents the value of b . It can be seen that in the cathodic reaction ( b = 0.722), the charge storage process is a hybrid mechanism, which is simultaneously controlled by both diffusion and capacitive surface reactions, whereas in the anodic reaction ( b = 0.987), the surface-controlled capacitive process has the dominant characteristics, , suggesting that the charge–discharge process in the p-CoNC@Si80 electrode has predominantly surface-controlled capacitive behavior.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A b -value of 0.5 indicates a diffusion-controlled process, whereas a b -value of 1 represents ideal surface-controlled capacitive behavior. The value of b can be obtained from the slope of the linear relationship between log­( i ) and log­( v ) plots according to the following equation Figure b shows the relationship between log­( i ) and log­( v ), where the linear slope represents the value of b . It can be seen that in the cathodic reaction ( b = 0.722), the charge storage process is a hybrid mechanism, which is simultaneously controlled by both diffusion and capacitive surface reactions, whereas in the anodic reaction ( b = 0.987), the surface-controlled capacitive process has the dominant characteristics, , suggesting that the charge–discharge process in the p-CoNC@Si80 electrode has predominantly surface-controlled capacitive behavior.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The value of b can be obtained from the slope of the linear relationship between log­( i ) and log­( v ) plots according to the following equation Figure b shows the relationship between log­( i ) and log­( v ), where the linear slope represents the value of b . It can be seen that in the cathodic reaction ( b = 0.722), the charge storage process is a hybrid mechanism, which is simultaneously controlled by both diffusion and capacitive surface reactions, whereas in the anodic reaction ( b = 0.987), the surface-controlled capacitive process has the dominant characteristics, , suggesting that the charge–discharge process in the p-CoNC@Si80 electrode has predominantly surface-controlled capacitive behavior. In addition, the charge contribution ratio of the surface-capacitive and diffusion controls can be calculated by dividing the response of the current at a specific potential by the following two-part equation where i (V) is the current response at a fixed potential V, v is the scan rate, k 1 v is capacitive control, and k 2 v 1/2 is diffusion control.…”
Section: Results and Discussionmentioning
confidence: 99%
“…− anions mainly occurs in carbonaceous materials, including graphite, graphene, metal organic framework (MOF) derivatives, and covalent organic framework (COF). [18][19][20][21][22][23][24][25] The reversible intercalation/deintercalation process of Al 3+ cations usually refers to some oxides, sulfides and selenides. [26][27][28][29][30][31] In recently reported research, AlCl 2…”
Section: Introductionmentioning
confidence: 99%
“…The reversible intercalation/deintercalation process of AlCl 4 − anions mainly occurs in carbonaceous materials, including graphite, graphene, metal organic framework (MOF) derivatives, and covalent organic framework (COF). [ 18–25 ] The reversible intercalation/deintercalation process of Al 3+ cations usually refers to some oxides, sulfides and selenides. [ 26–31 ] In recently reported research, AlCl 2 + cations can reversibly intercalate/deintercalate into/from organic materials, including phenanthrenequinone triangle (PQ‐Δ), poly(hexaazatrinaphthalene) (PHATN), polyimide, 2,3,5,6‐tetraphthalimido‐ p ‐benzoquinone (TPBQ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to develop high-performance HSCs with ultrastable cyclability that also have a simple metal electrode such as aluminum. Moreover, aluminum has a rich abundance and high energy density resulting from the three-electron redox process (i.e., the intercalation mechanism of the trivalent Al 3+ ion) caused by the oxidation of aluminum ions. In this regard, many studies have investigated aluminum-ion batteries (AIBs) and supercapacitors using various alloy anodes based on aluminum anode modification in various electrolytes (nonaqueous and aqueous electrolytes). For example, Wang et al demonstrated lamella-nanostructured eutectic zinc–aluminum alloys as reversible and dendrite-free anodes for aqueous zinc-ion batteries. The aqueous Zn 88 Al 12 /K x MnO 2 batteries were constructed with a eutectic Zn 88 Al 12 alloy sheet as the anode and K x MnO 2 as the cathode, achieving a specific capacity as high as ∼294 mA h g –1 and delivering a high energy density of 230 W h kg –1 while retaining 100% capacity after 200 h (5000 cycles) .…”
Section: Introductionmentioning
confidence: 99%